Ciało obce, obcość ciała. Jan Borowicz: Nagość i mundur. Ciało w filmie Trzeciej Rzeszy. Warszawa, Instytut Wydawniczy Książka i Prasa, 2015, ss. 161 - Janik, Gaweł (Narracje o Zagładzie [czasopismo zamknięte], 2016)
Foreign Body, Body’s Foreignness. Jan Borowicz: Nagość i mundur. Ciało w filmie Trzeciej Rzeszy. Warszawa, Instytut Wydawniczy Książka i Prasa, 2015, ss. 161. In his review, the author discusses Jan Borowicz’s monograph Nagość i mundur. Ciało w filmie Trzeciej Rzeszy, in which the Third Reich cinematography has been analysed in terms of the ways of depicting corporeality. The review discusses the methodology foregrounding the piece and notes the innovative character of not only the framing of the subject of study, but also numerous conclusions drawn from Borowicz’s research. All the three main parts of the monograph are analysed, describing the depictions of the Nazi body, the non‑German one, and the sick, monstrous and disfigured body of the Jew. The interdisciplinary character of the book is pointed at, since Nagość i mundur… connects the visual and film studies with the cultural, philosophical, sociological, as well as political and biopolitical perspectives.